TEST OF PREPARATION FORMULATION SPRAY MANGROVE LEAF EXTRACT RHIZOPORA MUCRONATA AS REPELLENT AGAINST MOSQUITO ANOPHELES VAGUS (Journal of Health, Technology and Science (JHTS), 2024)
The mangrove plant   Rhizopora mucronata  is a plant that belongs to the Family   Rhizophoraceae   and is often found in tidal areas, one of which is in Boalemo Regency, Bajo Village. This plant is used as a   repellent   on the leaves. The secondary metabolite compounds contained in the leaves of   Rhizopora mucronata   function as   repellent   namely alkaloids, flavonoids, tannins and terpenoids.    This study aims to determine the activity and significant differences in the concentration of the preparation formulation   spray   mangrove leaf extract   Rhizopora mucronata   as   repellent   against mosquitoes   Anopheles vagus.  Laboratory experimental research method with the research object being mangrove leaf extract   Rhizopora mucronata   which includes the maceration and extraction stages with methanol solvent, identification of secondary metabolite compounds, preparation evaluation test, and   repellent   test with 6 test groups, namely negative control, F0%, F10%, F15%, F20%, and positive control (soffel   spray  ).  The results of the study showed that the formulation   spray   mangrove leaf extract   Rhizopora mucronata   had activity against mosquitoes   Anopheles vagus  due to mangrove leaf extract   Rhizopora mucronata    contains alkaloids, tannins, flavonoids and terpenoids which function as   repellent  . The preparation formulation   spray   mangrove leaf extract   Rhizopora mucronata  concentrations of 10%, 15%, and 20% do not have a significant difference in effect on mosquitoes   Anopheles vagus, because     at this concentration the compound content of mangrove leaves   Rhizopora mucronata   is equally effective as   repellent   against mosquitoes   Anopheles vagus.